2017
DOI: 10.3126/njr.v4i2.18482
|View full text |Cite
|
Sign up to set email alerts
|

Study of Portal Vein Diameter and Spleen Size by Ultrasonography and Their Association with Gastro-esophageal Varices

Abstract: Introduction: Upper Gastro-intestinal endoscopy is considered the best screening tool for varices in cirrhotic patients. It is still an expensive, invasive tool, has poor compliance and not routinely available in every hospitals in Nepal. This study was undertaken to establish the role of portal vein diameter and spleen size by ultrasonography in predicting gastroesophageal varices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…Other international studies stated that the portal vein diameter was 10.8±1.14 mm which is close to the result of this study (11). The study did not mention any correlation with age, gender, weight, height or BMI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other international studies stated that the portal vein diameter was 10.8±1.14 mm which is close to the result of this study (11). The study did not mention any correlation with age, gender, weight, height or BMI.…”
Section: Discussionsupporting
confidence: 90%
“…Patient height and BMI are positively correlated with mean portal vein diameter (10). In Asia, a study done in Nepal was undertaken to establish the role of portal vein diameter and spleen size by ultrasonography in predicting gastro-esophageal varices revealed that portal vein diameter of patients without gastro-esophageal varices was smaller than in patients with varices (11). Table 1 summarizes the PVD in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Among 97 patients, 30 (30.9%) were in Child Turcotte Pugh class A, 30 (30.9%) in CTP class B and 37 (38.1 %) were in CTP class C. Small varices were found in 25 (8%) patients; 52% of patients had large varices with red color sign and 20.6% had large varices without red color sign [ 16 ]. In another study, the prevalence of esophageal varices was higher in CTP class C [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Whenever endoscopy cannot be performed due to any of these reasons certain non-invasive methods are recommended for detecting esophageal varices. 4,6,10 These alternate procedures include Doppler USG, CT, MRI and Angiography. 11 In addition to these Platelet count is also a noninvasive parameter with high accuracy for the prediction of esophageal varices as cirrhotic pts having esophageal varices usually have a platelet count of < 100,000/cmm.…”
Section: Guidelines Published By Baveno V1 Consensusmentioning
confidence: 99%